STRATEGI GURU TAHFIZ UNTUK MENINGKATKAN MINAT MENGHAFAL AL-QUR’AN SANTRI DARUL HAQ JAMBI - Mawar Lestari; Sukarno; Samsu (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study aims to analyze tahfiz teachers' strategies for increasing students' interest in Qur'an memorization at the MTs level in Darul Haq Islamic Boarding School, Jambi. A descriptive qualitative approach with a field research design was employed. Data were collected through participatory observation, semi-structured in-depth interviews, and document analysis, then processed using Miles & Huberman's interactive model. Findings reveal that effective tahfiz teacher strategies synergistically combine three approaches: an affective approach through personal motivation and emotional reinforcement, a spiritual approach through internalization of worship values and teacher role modeling, and a technical-methodical approach through the application of talaqqi, tikrar, tasmi', and muraja'ah methods. A religious boarding school environment and peer group support serve as the main facilitating factors, while dense schedules, methodological monotony, limited facilities, and disproportionate teacher-student ratios are the primary barriers. Recommendations include optimizing time management, diversifying instructional methods, improving teacher training, and strengthening family involvement in students' memorization process.